Penerapan Model Pembelajaran Contextual Teaching and Learning untuk Meningkatkan Keaktifan dan Hasil Belajar Siswa: Penerapan Model Pembelajaran Contextual Teaching And Learning Untuk Meningkatkan Keaktifan Dan Hasil Belajar Siswa - Luqman Abdul Azis; Slamet Priyanto; Samsul Hadi (JURNAL VOKASI DEWANTARA (JVD), 2022)
The research aims to: (1) Increase student learning activity; and (2) Improving the learning outcomes of Basic Job Automotive Engineering for class X TKR SMK Muhammadiyah Piyungan. This research is a Classroom Action Research (CAR) which consists of 3 cycles each consisting of four stages, namely: Action planning; Implementation of actions; Observation; and Reflection. The research subjects were 22 students of class X TKR SMK Muhammadiyah Piyungan, while the object of research was the activeness and learning outcomes of Basic Automotive Engineering. Data collection techniques using observation, tests and documentation. The data analysis technique uses quantitative analysis to determine the percentage of student activity and learning outcomes. The results showed that the application of the Contextual Teaching and Learning (CTL) learning model could increase the activeness and learning outcomes of Basic Work Automotive Engineering in class X TKR SMK Muhammadiyah Piyungan.